Design of compact and conformal rectennas - Xie, Zunbo (Nanyang Technological University, 2022)
A rectenna (rectifying antenna) is a special type of receiving antenna that is used to convert electromagnetic energy into direct current (DC) electricity. Rectennas are widely used in many internet of things (IoT) devices for sensing and communication purposes. The objective of this project is to design several rectennas that are compact and can be mounted on a conformal platform. The rectenna mainly consists of the receiving antenna and the rectifier circuit. In this dissertation, several antennas are designed in HFSS and simulated on a conformal plane, and the final design can generally operate in the 902-928 MHZ band range. Furthermore, according to the requirement of load voltage and RF to DC conversion efficiency, some suitable rectifier circuits are designed using ADS.